주조공정 설계를 위한 자연주물사와 인공주물사의 열물성 시험 - 남정호; Jeong-ho Nam; 이병준; Byoung-jun Lee; 곽시영; Si-young Kwak (한국주조공학회지, 2024)
최근에는 주조업계의 중요한 과제로써 산업폐기물 저감 과 대기환경 개선이 부각되고 있다. 종래의 주물사 사용 시 발생되는 문제점 해결과 주조공장의 환경개선을 위해 천연사를 대체 적용할 수 있는 다양한 인공사가 개발되어 사용되고 있다. 하지만 해외 공급사에서 제공하는 제한된 물성만 알려져 있고 기존 자연사와의 심층적인 비교분석이 부족하다. 또한 주조 공정 설계를 위해서는 상온뿐만 아니라 고온에서의 넓은 범위의 열물성이 확보 되어야 하며, 또한 열물성이 달라지면 주조방안 설계의 변화가 일어나야 하기 때문에 기존 자연사와 인공사의 열물성 차이를 비교 분석하는 건 중요하다. 본 연구에서는 자연사와 인공사를 바인더와 결합한 주형블럭에서의 열전도도, 비열, 열팽창 시험을 수행하였으며 실험 결과 열전도도는 자연사에 비해 인공사가 구성성분에 따라 5~40% 높았으며 열팽창계수는 인공사가 15%정도 낮았다. 하지만 비열은 구성성분에 상관없이 큰 차이가 없었다. Reducing industrial waste and improving the atmospheric environment recently have emerged as important tasks for the casting industry. Various types of artificial sand that can replace natural sand have been developed and used to solve problems that arise with the use of conventional foundry sand and to improve the foundry environment. However, only limited physical properties provided by overseas suppliers are known and in-depth comparative analyses with existing natural sand are lacking. For the design of the casting process, a wide range of thermal properties must be secured not only at room temperature but also at high temperatures. In addition, it is important to compare and analyze the differences in thermal properties between existing natural and artificial sand because changes in thermal properties require changes in the design of the casting method. In this study, the thermal behavior of the mold was analyzed through a thermal expansion test of mold blocks for natural and artificial sand., To this end, a thermal property test to evaluate thermal conductivity was performed by determining a temperature range. The results of the experiment, revealed that the thermal conductivity was 5-40% higher in artificial sand than in natural sand, and the coefficient of thermal expansion was about 15% lower for artificial sand. However, there was not a significant difference in specific heat regardless of the composition.